The Effectiveness of Influencer Marketing, Content Marketing, and Electronic Word of Mouth (E-WoM) on Purchasing Decisions for Beauty Products on Shoope Live Streaming - Dhea Ariesta; Lilik Indayani; Rita Ambarwati Sukmono (Yayasan Riset dan Pengembangan Intelektual, 2024)
Selling products via live streaming is something that is increasingly in demand, therefore business actors continue to improve their skills to attract consumers in live streaming sales. This research aims to describeinfluence of the effectiveness Influencer Marketing, Content Marketing, and Electronic Word of Mouth (E-WOM) on Beauty Product Purchasing Decisions on Shoope Live Streaming. With a sample of 100 Shopee application users who have purchased beauty products via live streaming. This research uses quantitative research with a data analysis method using Partial Least Square (PLS) with the Smart-PLS program. The research results show that Influencer Marketing, Content Marketing and Electronic Word of Mouth (E-WOM) has a positive and significant effect on Beauty Product Purchasing Decisions on Shope Live Streaming, so that all hypotheses in this research are accepted. So it is revealed that the variables Influencer Marketing, Content Marketing, and Electronic Word of Mouth can be said to have strong implications for Beauty Product Purchasing Decisions on Shopping Live Streaming. With this, it is hoped that business actors will try to improve the quality of their live streaming so they can attract buyers.